NEW MOLECULAR MECHANISM OF CEFTAZIDIME-INDUCED HUMAN RED BLOOD CELL HEMOLYSIS THROUGH THE PHOTOHEMOLYSIS REACTION - Mashuri, Mashuri; Zaini, Achmad; Rahmanisa, Diana; Alfiannoor, Muhammad Rifqi; Sanjaya, Muhammad Rosyhan; Suhartono, Eko (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was undertaken to investigate the photohemolysis reaction through photosensitization reaction by ceftazidime as a photosensitizer in human red blood cell (RBC). Methods: In this present study, human erythrocytes have used a sample. The sample then divided into six groups consisting of Group 1 (T1) served a negative control which consists of erythrocytes and buffers phosphate with pH 6.8; Group 2 (T2) served as a positive control which consists erythrocytes and buffers phosphate with pH 6.8 and exposed to UV-light; and Group 3, 4, 5, and 6 (T3, T4, T5, and T6) served as an experimental group which consists of erythrocytes, buffer phosphate with pH 6.8, ceftazidime with concentration 10%, 20%, 30%, and 40%, respectively, and also exposed to UV-light. UV-light exposure was done in 2 h. After the treatment period, the level of hydrogen peroxide (H2O2), conjugated diene (CD), advanced oxidation protein products (AOPPs), and percentage of RBC hemolysis (RBCH) were measured. Results: The results of this present studies showed that ceftazidime significantly increases the levels of H2O2, CD, AOPPs, and percentage of RBCH during the UV radiation. Conclusion: The present study demonstrated that ceftazidime acts as a photosensitizer and induced the photohemolysis reaction in human RBC. Furthermore, the hemolysis of RBC seems through the protein damage than lipid damage.